2018
DOI: 10.1101/368555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lmx1a drives Cux2 expression in the cortical hem through activation of a conserved intronic enhancer

Abstract: During neocortical development, neurons are produced by a diverse pool of neural progenitors. A subset of progenitors express the Cux2 gene and are fate-restricted to produce certain neuronal subtypes, but the upstream pathways that specify these progenitor fates remain unknown. To uncover the transcriptional networks that regulate Cux2 expression in the forebrain, we characterized a conserved Cux2 enhancer that we find recapitulates Cux2 expression specifically in the cortical hem. Using a bioinformatic appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…To our knowledge, there are no currently available data showing specific binding of 5caC-marked DNA, for TCF4 or any other transcription factor, in a cellular context. Genes potentially regulated directly by the binding of TCF4 include CNIH3 , a gene involved in opioid dependence (68), LMX1A, a LIM homeobox transcription factor that drives Cux2 expression in the forebrain (69), TRIM8, an E3 ubiquitin ligase that regulates glioma-driving genes and functions related to the central nervous system (70), IDH2, a key metabolic enzyme that generates α-ketoglutarate, and TET1, one of the three 5mC dioxygenases that uses α-ketoglutarate as enzymic cofactor (Supplementary Figure S3C). It remains to demonstrate, in a cellular context, that the regulation of gene expression at these loci involves TCF4 binding to DNA marked by 5caC.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no currently available data showing specific binding of 5caC-marked DNA, for TCF4 or any other transcription factor, in a cellular context. Genes potentially regulated directly by the binding of TCF4 include CNIH3 , a gene involved in opioid dependence (68), LMX1A, a LIM homeobox transcription factor that drives Cux2 expression in the forebrain (69), TRIM8, an E3 ubiquitin ligase that regulates glioma-driving genes and functions related to the central nervous system (70), IDH2, a key metabolic enzyme that generates α-ketoglutarate, and TET1, one of the three 5mC dioxygenases that uses α-ketoglutarate as enzymic cofactor (Supplementary Figure S3C). It remains to demonstrate, in a cellular context, that the regulation of gene expression at these loci involves TCF4 binding to DNA marked by 5caC.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that there is a distinct set of MP TFs, such as those found in our screen, Id3 and Lmx1a, that promote the activity of MP enhancers (Fig. 1) (45). Thus, we have shown that the combination of EMX2, LHX2, NR2F1, PAX6, and PBX1 binding in pREs provided a signature that was predictive of pRE regional activity and cortical gradients.…”
Section: Discussionmentioning
confidence: 51%
“…This bias is not due to expression of the TFs ( Emx2, Lhx2, Nr2f1 and Pax6 are expressed in the MP), nor is it entirely due to a bias in cell numbers since LVP and MP are both small structures in comparison to the DP, which had a level of TF binding intermediate to that of the LVP and MP. We propose that there is a distinct set of MP TFs, such as those found in our screen, Id3 and Lmx1a , that promote the activity of MP enhancers (Figure 1; Fregoso et al, 2019). Thus, we have shown that the combination of EMX2, LHX2, NR2F1, PAX6 and PBX1 binding in pREs provided a signature that was predictive of pRE regional activity and cortical gradients.…”
Section: Discussionmentioning
confidence: 77%